Identification of Stakeholders in Research Projects, a perspective from the University of Cundinamarca - Colombia - Valencia Achuri, Paola Andrea (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
The present exploratory study carried out an analysis of the management of Stakeholders in research projects at the University of Cundinamarca - Colombia, establishing key Stakeholders and their relational level, applying the methodology of social network analysis with the UCINET software. Among the main results, the Stakeholders ecosystem, relationship maps and cluster stand out, which allowed identifying key Stakeholders at the management level, with whom the research resources are managed, at the operational level, with whom it collaborates to develop research activities, and at the social level, on whom the research results are deployed.